2003
DOI: 10.1016/s1063-4584(03)00078-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement accuracy of focal cartilage defects from MRI and correlation of MRI graded lesions with histology: a preliminary study

Abstract: Three-dimensional mapping of cartilage thickness shows great promise for the accurate measurement of focal cartilage defects, though improvement is needed. The Noyes grading scale is consistent with histological Mankin grading of cartilage lesions, though enhancement of MR grading scales is needed, and warranted, based on the signal intensity information available from clinical MRI. Integration of these two analyses-focal defect measurement and signal intensity analysis-could potentially result in a valuable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 37 publications
2
52
3
Order By: Relevance
“…Lesions found and staged with arthroscopy are more likely to be detected using MRI (due to larger size) than those found using histology. The relatively lower sensitivity to lesions in our study might also be in part due to our exclusive use of sagittal MRI images for detection and evaluation of cartilage lesions, whereas others have used multiple planes to locate and stage abnormalities [8,26,27].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Lesions found and staged with arthroscopy are more likely to be detected using MRI (due to larger size) than those found using histology. The relatively lower sensitivity to lesions in our study might also be in part due to our exclusive use of sagittal MRI images for detection and evaluation of cartilage lesions, whereas others have used multiple planes to locate and stage abnormalities [8,26,27].…”
Section: Discussionmentioning
confidence: 75%
“…Loss of cartilage thickness was predicted with 72% sensitivity and 69% specificity; however, sensitivity for cartilage surface integrity was lower and specificity was higher (69% and 74%, respectively). While others have assessed the diagnostic performance of MRI for cartilage lesions using histology [25][26][27][28][29][30], few [9,10,22] have determined the diagnostic performance of FSE sequences with comparison to histology. Our outcomes are comparable to some, but slightly lower than the findings of other investigators in sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McGibbon and Trahan (115) found the mean difference between measured and actual artificial cartilage defect diameters in the human knee cartilage to be <0.1 mm, whereas the lesion depth was underestimated in MRI by >0.4 mm. Graichen et al (128) observed an overestimation of the true size of artificial cartilage defects in the human knee, which decreased from 42% in 3 mm defects to 4% in 8 mm defects.…”
Section: Technical Accuracy and Precision Of Measurementsmentioning
confidence: 99%
“…In order to track local/regional thickness changes over time, techniques for displaying regional thickness patterns have been developed (91,94,100,(113)(114)(115). These techniques have also been applied to the detection of cartilage lesions, but only a limited number of thickness intervals can be displayed with a limited number of color codes or gray levels.…”
Section: Image Analysis Techniquesmentioning
confidence: 99%